2022
DOI: 10.1097/sla.0000000000005423
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Course of Low-anterior Resection Syndrome

Abstract: Objective:We aimed to better understand the longitudinal course of low anterior resection syndrome (LARS) to guide patient expectations and identify those at risk of persisting dysfunction.Summary Background Data:LARS describes disordered bowel function after rectal resection that significantly impacts quality of life.Methods:MEDLINE, EMBASE, CENTRAL, and CINAHL databases were systematically searched for studies that enrolled adults undergoing anterior resection for rectal cancer and used the LARS score to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…6 A meta-analysis suggested that the mean LARS score improved mostly within 18 months after surgery (from 29.4 to 20.4) and remained relatively stable from 18 to 36 months (20.4 vs 16.6). 5 Continuous LARS improvement was also observed in a cohort of 107 patients, mostly without neoadjuvant radiotherapy, with a 45% improvement in major LARS at 20 months and a 24% improvement at 38 months. 15 Over a longer time frame, serial follow-ups of 282 patients at 6.1 and 11.1 years showed slight improvement (53%-49%) in major LARS.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…6 A meta-analysis suggested that the mean LARS score improved mostly within 18 months after surgery (from 29.4 to 20.4) and remained relatively stable from 18 to 36 months (20.4 vs 16.6). 5 Continuous LARS improvement was also observed in a cohort of 107 patients, mostly without neoadjuvant radiotherapy, with a 45% improvement in major LARS at 20 months and a 24% improvement at 38 months. 15 Over a longer time frame, serial follow-ups of 282 patients at 6.1 and 11.1 years showed slight improvement (53%-49%) in major LARS.…”
Section: Discussionmentioning
confidence: 73%
“…4 It is generally believed that symptoms of LARS improve within 1 to 2 years after surgery and remain stable afterward. 5,6 However, this is yet to be determined because long-term serial follow-up is lacking. In addition, patients who received ostomy because of severe postoperative dysfunction were often excluded by previous studies, impeding accurate assessment of the long-term impact of LARS.…”
Section: Principales Mediciones De Resultadomentioning
confidence: 99%
“…The POLARS score was developed in a retrospective cohort from the UK and validated in a retrospective cohort from Denmark 9. Previously, it has been shown that LARS stabilises after 1.5 years and remains constant thereafter 17. The follow-up time in the UK (5.2 years), Danish (4.7 years) and the current study (6.7 years) are all longer than that, therefore the difference in follow-up time should not affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…Oncological and surgical changes in the management of rectal cancer have occurred during this time. Preoperative RT is a known risk factor for postoperative bowel function following low anterior resection17 and there are differences in the treatment protocols for neoadjuvant RT. The proportion of patients receiving preoperative RT was 32% and 20% in the UK and Danish cohorts, respectively9 compared with a significantly higher proportion in the Swedish cohort, 67%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation